The causeway that leads to the Ghateshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Ghateshwar Temple is part of a group of eight temples known as the Baroli group of temples. There are two clusters in the complex. The first cluster is situated near the present entrance to the complex, provided by the Archaeological Survey of India (ASI). The second cluster which includes the Ghateshwar Temple, is situated at the backside of the complex. A causeway leads to the second cluster from where a glimpse of the Ghateshwar Temple can be seen.